1305. Comparison of Pharmacokinetics of DSTA4637S, a novel THIOMABTM Antibody-Antibiotic Conjugate, in Patients with Staphylococcus aureus Bacteremia Receiving Standard-of-Care Antibiotics with Pharmacokinetics in Healthy Volunteers. (31st December 2020) - Rymut, Sharon M; Deng, Rong; Owen, Ryan; Saad, Ola; Berhanu, Aklile; Lim, Jeremy; Carrasco-Triguero, Montserrat; Couch, Jessica A; Peck, Melicent C
Abstract: Background: DSTA4637S, a THIOMAB TM antibody-antibiotic conjugate against Staphylococcus aureus, is a potential therapy for complicated S. aureus bacteremia. Single doses showed favorable safety and pharmacokinetics (PK) in healthy volunteers (HVs). This study compares HV PK results to PK from a Phase 1b study evaluating multiple doses in patients with bacteremia. Methods: In a Phase 1a study, HVs received single intravenous (IV) doses (5, 15, 50, 100, or 150 mg/kg) of DSTA4637S. The Phase 1b, randomized, double-blind, placebo-controlled, multiple ascending-dose study enrolled patients with MRSA or MSSA bacteremia receiving ≥ 4 weeks of standard-of-care (SOC) antibiotics in combination with IV DSTA4637S (15, 45, or 100 mg/kg) weekly (4-6 doses). Intensive PK serum and plasma sampling was performed after first and last doses of DSTA4637S. Total antibody (TAb) was measured in serum by ELISA. DSTA4637S conjugate (ac-dmDNA31) and unconjugated dmDNA31 were measured in plasma with IA-LC-MS/MS and LC-MS/MS, respectively. DSTA4637S PK was analyzed using a non-compartmental approach using WinNonlin. Results: DSTA4637S PK data were evaluated in 20 HVs in the Phase 1a study and 19 patients with S. aureus bacteremia in the Phase 1b study. In both HVs and patients, systemic exposures of TAb and ac-dmDNA were generally dose proportional over the dose ranges tested. In patients compared to HVs, Cmax, cycle 1 for ac-dmDNA31 and TAb were reduced 26.7-51.3% and 32.4-44.1%, respectively, contributing to lower patient AUC0-7 . Unconjugated dmDNA31 concentrations were low (< 11 ng/mL), peaking 1-2 days after dosing, in both studies. There was no clear association between DSTA4637S exposure (ac-dmDNA31) and demographic factors (age, weight, sex), clinical status (bacteremia at dosing, infection site), adverse events (infusion-related reactions), or exploratory biomarkers (CRP, procalcitonin, inflammatory cytokines). Conclusion: DSTA4637S PK analysis demonstrated lower exposures in patients with S. aureus bacteremia compared to HVs. Potential explanations for reduced exposures include factors related to disease status, non-specific organ uptake, and target-mediated clearance. Disclosures: Sharon M. Rymut, PhD, Genentech (Employee, Shareholder) Rong Deng, PhD, Roche (Consultant, Employee, Shareholder) Ryan Owen, PhD, Genentech (Employee, Shareholder) Ola Saad, PhD, Genentech - Roche (Employee) Aklile Berhanu, PhD, Genentech, Inc. (Employee, Equity interest (Stock/Stock Options)) Jeremy Lim, PharmD, Roche (Employee, Shareholder) Montserrat Carrasco-Triguero, PhD, Genentech (Employee) Jessica A. Couch, PhD, Genentech (Employee, Shareholder) Melicent C. Peck, MD, PhD, Genentech (Employee)